Early parenteral nutrition in critically ill patients with short-term relative contraindications to early enteral nutrition: a full economic analysis of a multicenter randomized controlled trial based on US costs - Doig GS; Simpson F (Dove Medical Press, 2013)
Gordon S Doig, Fiona Simpson, On behalf of the Early PN Trial Investigators GroupNorthern Clinical School Intensive Care Research Unit, University of Sydney, Sydney, NSW, AustraliaPurpose: The provision of early enteral (gut) nutrition to critically ill patients, started within 24 hours of injury or intensive care unit admission, is accepted to improve health outcomes. However, not all patients are able to receive early enteral nutrition. The purpose of the economic analysis presented here was to estimate the cost implications of providing early parenteral (intravenous) nutrition to critically ill patients with short-term relative contraindications to early enteral nutrition.Materials and methods: From the perspective of the US acute care hospital system, a cost-minimization analysis was undertaken based on large-scale Monte Carlo simulation (N = 1,000,000 trials) of a stochastic model developed using clinical outcomes and measures of resource consumption reported in a 1,363-patient multicenter clinical trial combined with cost distributions obtained from the published literature. The mean costs of acute care attributable to each study group (early parenteral nutrition versus pragmatic standard care) and the mean cost difference between groups, along with respective 95% confidence intervals, were obtained using the percentile method.Results and conclusion: The use of early parenteral nutrition in critically ill patients with short-term relative contraindications to early enteral nutrition may significantly and meaningfully reduce total costs of acute hospital care by US$3,150 per patient (95% confidence interval US$1,314 to US$4,990). These findings were robust, with all sensitivity analyses demonstrating significant savings attributable to the use of early parenteral nutrition, including sensitivity analysis conducted using European cost data.Keywords: intensive care, acute hospital care, intravenous nutrition, US acute hospital system